2021
DOI: 10.3889/oamjms.2021.6423
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Grading Histopathology and Sentinel Lymph Node Metastasis in Early Breast Cancer in University of Sumatera Utara Hospital

Abstract: BACKGROUND: Breast cancer is a malignancy in breast tissue from the duct or lobar epithelium. American Joint Committee on Cancer has specified important prognostic factors such as primary tumor size, regional lymph node status, and distant metastasis. Axillary lymph node status has been one of the most reliable prognostic factors in early breast cancer in women. Axillary lymph node dissection is an old method to identify metastasis in axillary lymph nodes and started being replaced by sentinel lymph node biops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The study revealed a significant relationship between the grade variable and the occurrence of metastasis to lymph nodes in breast cancer, as determined by the chi-square test results. In the present study, the variable "grade" is identified as one of the ten factors influencing breast cancer metastasis to lymph nodes (33). In their study, Li et Consequently, it is probable to consider that the factors that impact the survival of breast cancer patients may also influence the occurrence of lymph node metastasis in these individuals (37).…”
Section: Discussionmentioning
confidence: 91%
“…The study revealed a significant relationship between the grade variable and the occurrence of metastasis to lymph nodes in breast cancer, as determined by the chi-square test results. In the present study, the variable "grade" is identified as one of the ten factors influencing breast cancer metastasis to lymph nodes (33). In their study, Li et Consequently, it is probable to consider that the factors that impact the survival of breast cancer patients may also influence the occurrence of lymph node metastasis in these individuals (37).…”
Section: Discussionmentioning
confidence: 91%
“…Considering the modified Bloom—Richardson grading system or Nottingham grading system, our study showed that majority of tumor including 110 (91.7%) patients were IDC, NOS, 65 (54.2%) were grade 2 and 44 (36.7%) were intermediate size (2–5 cm), which is consistent with the result of Cherry Bansal found in Indian papulation in which 56.2% of the tumor were intermediate in size (2–5 cm) and 64% were IDC, NOS grade 2 [ 30 ]. There is a relation between grade of tumor and metastasis to axillary lymph nodes, high-grade tumors have more sentential lymph node metastasis [ 31 , 32 ]. Multiple clinicopathologic factors affect prognosis and therefore the outcome of management in patients with BC, including histological type, grade, stage, status of ER, PR and Her2/neu, BRCA 1 status [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%